Global Trends in Green Finance in the Banking Sector: A Bibliometric Mapping of Past and Future Research Directions - Rusdi Hidayat Nugroho; Indah Respati Kusumasari; Nugraha Kusbianto; Nurhadi Nurhadi; Lusi Kurnia (Politeknik Siber Cerdika Internasional, 2026)
Background: This analysis is a systematic review of green finance in the banking sector, combining information from 193 papers published in 126 journals indexed in Scopus between 2020 and 2025. Objective: To provide a broad reference source for future research and a better understanding of the interaction between banks, environmental protection, climate change, and the 2030 Sustainable Development Goals. The most recent contributions in green banking—mitigation of risk, technology, credit policy, and ethical practices within organizations—are pointed out. Methods: Quantitative analysis based on bibliometric methodology of the Scopus database with search string TITLE-ABS-KEY(